RINA Small Craft Group International Conference : Computer Aided Design and Production for Small Craft at Novotel, Southampton, 26 & 27 September 1995 - International Conference on Computer Aided Design and Production for Small Craft (1995 : Southampton, UK); Royal Institution of Naval Architects (Great Britain). Small Craft Group (London : Royal Institution of Naval Architects, 1995)
19